The many faces of endometriosis - Marcelo Luis Pereira de Souza Filho; Talita Porto da Costa; Nathanael Pinheiro de Freitas Junior; Maiara Ferreira de Souza; Daniel Abensur Athanazio (University of São Paulo, 2022)
Endometriosis is a common disease; however, unusual findings may cause diagnostic difficulties. We present herein three cases illustrating different morphological appearances of endometriosis: 1) endometriosis with atypical hyperplasia associated with bilateral ovarian carcinoma (mixed clear cell/endometrioid in the left ovary and endometrioid in the right ovary); 2) deep infiltrating endometriosis with intravascular spread, polypoid configuration in peritoneal surfaces, and involvement of a lymph node; and 3) decidualized endometriosis with prominent myxoid/mucinous change and multivacuolated (pseudoxanthoma) cells. Awareness of uncommon morphological manifestations of endometriosis is important to avoid improper consideration of malignancy.